Optimization of factors influencing temperature rise and thermal necrosis of a robot driven piezoelectric osteotomy in bovine cortical bone: An in vitro study using an orthogonal test design. (December 2019) - Tang, Hao; Deng, Wang; Sun, Zhibin; Wang, Yu; Li, Lan; Ding, Yi; Zhou, Yixin
Abstract: Background: This study aimed to provide a comprehensive investigation into factors influencing the thermal effect in robot assisted osteotomies utilizing a piezoelectric osteotome and to identify an optimal combination of factors that minimize the thermal effect in an orthogonal experimental design. Methods: Fresh bovine cortical bone was cut under standardized conditions using a robot arm, a piezoelectric osteotome, and a cooling system. Temperature was monitored and the histological depth of osteocyte thermal necrosis was examined to quantify the thermal effect(s). Eighteen experimental trials were conducted according to the standard L18 (2 1  × 3 7 ) orthogonal design table to explore the roles of 6 factors: power of the piezoelectric osteotome, cutting depth, cutting speed, coolant type, coolant flow velocity, and coolant temperature. Findings: Our data showed that coolant flow velocity, coolant temperature and cutting speed significantly influenced temperature ( p  < .05), while no significant temperature increase was identified relating to cutting depth, power of the piezoelectric osteotome and coolant type. The findings of histological osteocyte thermal necrosis correlated with the results of the temperature change. Interpretation: Coolant flow velocity, coolant temperature and cutting speed were key factors influencing the thermal impact of the piezoelectric osteotome. With proper combination of these 3 factors, a piezoelectric osteotome is safe to use from a thermal perspective. Highlights: Robot assisted piezosurgical osteotomy has significant temperature rise. Depth and percentage of histological osteonecrosis correlates to temperature rise. Six factors were explored to minimize temperature rise. Coolant flow velocity, coolant temperature and cutting speed are the key factors. Thermal necrosis can be minimized to below 47 °C with proper settings.